Regional strategies serving competitiveness - Eperjesi, Zoltán (Acta Agraria Debreceniensis, 2013)
In my study titled “Regional strategies serving competitiveness”, I examine the regional strategies whose development and implementation in practice play a determinant role in the medium- and long run economic and social development of the given region. The study primarily focuses on the infrastructural basic investments that are essential from the aspect of creating a knowledge-based information society. The study also deals with a stakeholder analysis used by investors in order to focus on the quality of state administration and institution system.